Light scattering effect of polyvinyl-alcohol/titanium dioxide nanofibers in the dye-sensitized solar cell - Mustafa, Muhammad Norhaffis; Shafie, Suhaidi; Wahid, Mohd Haniff; Sulaiman, Yusran (Nature Research, 2019)
In the present work, polyvinyl-alcohol/titanium dioxide (PVA/TiO2) nanofbers are utilized as a light scattering layer (LSL) on top of the TiO2 nanoparticles photoanode. The TiO2 nanoparticles decorated PVA/TiO2 nanofbers display a power conversion efciency (PCE) of 4.06%, which is 33% higher than TiO2 nanoparticles without LSL, demonstrating the incorporation of PVA/TiO2 nanofbers as LSL reduces the radiation loss and increases the excitation of the electron that leads to high PCE. The incorporation of PVA/TiO2 nanofbers as LSL also increases the electron life time and charge collection efciency in comparison to the TiO2 nanoparticles without LSL.